Can I Pay at Purgatory? The Negative Impact of the Purgatory Ethic in Islamic Societies: Theoretical and Empirical Evidence - Al-Issa, Riyad Salim (Religions, 2022)
The psychological and social effects of the doctrine of purgatory (temporary afterlife punishment) have not received sufficient attention from sociologists. Temporary afterlife punishment (TAP) is any kind of ‘temporary’ torment a person believes they will receive after death as a result of one’s sins, before admission into heaven/paradise. Investigating the effects of TAP beliefs can help to understand their social impact on contemporary Islamic societies. Drawing on related research on the Protestant ethic hypothesis, and self-control theory, the present study theorized the negative psychological and social impact of TAP. We argue that the effect of the Predestination doctrine on pro-sociality is best attributed to the Protestant denial of belief in TAP, and that the positive impact of afterlife punishment beliefs on self-control and prosocial behavior decreases with belief in TAP. To test these hypotheses, we first developed the Temporary Afterlife Punishment Expectations (TAPE) scale and examined the relationship between TAPE and self-control, rule-breaking ability, and integrity (as an indicator of prosocial behavior). Data were collected from Muslim youth in two countries (Jordan N = 605 and Malaysia N = 303). Exploratory and confirmatory factor analyses of the Jordanian data support the construct validity of the TAPE scale. In line with our hypotheses, path analysis results supported the negative effects of TAPE on self-control, rule-breaking ability, and integrity. Replicating the study with the Malaysian sample led to similar results. Future research directions are recommended.